Effects of tropical storm on equatorial Kelvin waves: a study based on both observation and modeling - Chu, Yubin; Deng, Zengan; Yu, Ting (Frontiers in Marine Science, 2023)
Tropical cyclones (TCs) play an important role in sea‐air interactions and cross-scale impacts on El Niño–Southern Oscillation events by influencing the turbulent mixing and heat distribution in the upper ocean. Utilizing the observational data and simulations from a numerical model with modified surface wind forcing, this study systematically investigates the effects of a tropical storm (TS) on equatorial Kelvin waves based on TS Dujuan, which is a low-intensity TC. Observations of anomalies combined with the equatorial wave decomposition method are used to confirm the passage of a downwelling Kelvin wave during the same period with properties similar to those of the modeled wave. Modeling results indicate that the TS amplifies the equatorial Kelvin wave, raising the sea surface height by ~2.1 cm and the upper ocean temperature by ~0.34°C and accelerating the eastward zonal current. These signals propagate eastward with the wave and decrease rapidly, and finally decrease to approximately 3-35% of their original strength, particularly the temperature decrease is greatest. Our findings reveal that, in the region close to the equator, even low-intensity cyclones like TS Dujuan can significantly impact the dynamics and propagation of Kelvin waves. TS Dujuan is capable of altering the thermal structure and momentum budget of the equatorial Pacific by amplifying the Kelvin waves. As TS Dujuan occurred during a La Niña event, we infer from our specific study that the forcing effects of TS on equatorial Kelvin waves may reduce the duration of La Niña events.